EFFECT OF BORAX ON SETTING TIME OF GEOPOLYMER CONCRETE BASED ON FLY ASH TYPE C - Septia Wulandari; Liana Herlina (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2022)
Geopolymer concrete is a new type of concrete that does not use cement as a binder at all. In addition to replacing cement, the use of fly ash in concrete can reduce coal emissions from many coal-fired power plants. However, geopolymer concrete has drawbacks, one of which is that it has a setting time that tends to be too fast. Therefore, this study aims to determine the effect of adding borax on the hardening time and compressive strength of geopolymer concrete. With the addition of 1%, 3%, 5%, and 10% borax. The ratio of activator Na2SiO3 and NaOH is used 2.5:1 with a molarity of 10M NaOH. Variations in the addition of borax during mixing include 1%, 3%, 5% and 10% by weight of fly ash. The test results showed that the higher the borax content added, the longer the setting time. The longest final setting time was achieved in geopolymer concrete with the addition of 10% borax for 480 minutes.